Experience of Crisis-Hit Asian Countries: Do Asset Management Companies Increase Moral Hazard? - Akiko Terada-Hagiwara; Gloria O. Pasadilla (Philippine Institute for Development Studies (PIDS), 2004)
This paper attempts to examine the performances of Asian AMCs. Our analysis reveals that the AMCs vary significantly in their design and performances. We claim that AMCs can trigger moral hazard-inspired bank lending, especially when the mode of NPL transfer from banks to AMC entails little cost to banks. Empirical examination of Thai experience of AMCs reveals that the moral hazardinspired bank lending resulted in creating more new NPLs in the case of public AMCs. On the other hand, the new centralized AMC, the Thai Asset Management Company (TAMC) decreases the new NPL ratio, suggesting that TAMC provokes no adverse moral hazard effect on financial institutions. In addition, we find that the same institutional consideration significantly decreases new NPL in foreign banks and finance companies. The former because they are generally considered better managed, and the latter because they are the institutions that survived the Asian crisis, and hence the more viable and presumably better run finance companies.
Keywords: 330; Asian financial crisis; bank restructuring; asset management company (AMC); Thailand; moral hazard; Vermögensverwaltung; Finanzsystem; Moral Hazard; Asien; Thailand; Finanzkrise